A LC–MS/MS method for therapeutic drug monitoring of carbamazepine, lamotrigine and valproic acid in DBS. (September 2015) - Linder, Camilla; Andersson, Maria; Wide, Katarina; Beck, Olof; Pohanka, Anton
Background: Therapeutic drug monitoring of antiepileptic drugs in children with epilepsy assists for personalized drug therapy but require numerous patient visits for venous blood sampling. DBS is an alternative matrix applicable to home sampling which can save time and reduce stress for this patient group.Results: A fast LC–MS/MS method for quantification of carbamazepine, lamotrigine and valproic acid based on DBS sampling was developed. The method showed linearity in therapeutically relevant concentration ranges and compatible with unknown volume sampling and expected hematocrit range of the patient group.Conclusion: A LC–MS/MS method for the three most commonly used antiepileptic drugs has been fully validated and clinically applied on DBSs from patients at the neuropediatric clinic at Karolinska University Hospital.